(AI) القضايا الأخلاقية في الذكاء الاصطناعي - هشام جاد الله منصور شخاترة; إسراء محمد عبابنة (University Of Eloued جامعة الوادي, 2023)
This paper provides a brief overview of ethical issues related to the use of artificial intelligence (AI). With the rapid advancement of AI technologies, concerns have arisen about its impact on society, including issues of privacy, bias, accountability, and job exclusion. These ethical considerations are important to address in the development and deployment of artificial intelligence (AI) systems to ensure that they are used in a responsible and beneficial manner. This paper highlights the critical ethical issues in the use of artificial intelligence and addresses the need for continued dialogue and collaboration among technologists, policy makers, and other stakeholders to ensure that artificial intelligence (AI) is developed and used in a manner that respects ethical principles and protects the interests of individuals and society as a whole.
Ethical issues in the use of artificial intelligence (AI)
مداخلة
Keywords: الذكاء الإصطناعي (AI); الخوارزميات; اتخاذ القرار المتحيز; قضايا الخصوصية; التحيز المساءلة; استبعاد الوظائف; الشفافية والمساءلة; artificial intelligence (AI); algorithms; biased decision making; privacy issues; bias; accountability; job exclusion; transparency and accountability